Shape-stabilized phase change material as well as preparation and application thereof

By using epoxy resin, curing agent and composite phase change materials, the problem of unstable shape and difficulty in setting of existing phase change materials is solved, and the regulation of shape stability and phase change performance is achieved, and it is suitable for applications in multiple fields.

CN119899489APending Publication Date: 2025-04-29DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311409323.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing phase change materials have problems of unstable shape and difficulty in shape in applications, which affects their wide application in the fields of architecture, electronics, etc.

Method used

The shaped phase change material is prepared by using epoxy resin, curing agent and composite phase change material (such as tetradecane microcapsules) as raw materials. The material remains consistent in shape before and after melting, and the phase change temperature and phase change enthalpy are adjustable.

Benefits of technology

The shape stability and phase change performance of phase change materials are realized, the preparation process is simplified, the production efficiency is improved, and the cost and time loss is reduced. It is suitable for applications in construction, electronics and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004517611210000011
    Figure HDA0004517611210000011
  • Figure HDA0004517611210000012
    Figure HDA0004517611210000012
Patent Text Reader

Abstract

The invention discloses a shape-stabilized phase-change material and a preparation method thereof.The shape-stabilized phase-change material is prepared from epoxy resin, a curing agent and a composite phase-change material through a series of processes such as stirring and mixing, and the formed shape-stabilized phase-change material has phase-change temperature adjustability and stability; the material can be randomly kneaded and deformed before being shaped, has certain strength after being shaped, meanwhile, based on the phase change performance of the material, the shape of the material is kept consistent before and after melting, and the situation of phase change material leakage is avoided; the preparation process is simple, production is convenient, the production efficiency is improved, the cost and time loss are reduced, and the method can be used for manufacturing phase change temperature control bricks and the like in the field of phase change buildings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a shapeable phase change material and a preparation method thereof, in particular to a phase change material which can be formed once and can be shaped according to a mold and a preparation method thereof. Background Art

[0002] Phase Change Materials (PCM) are a class of substances that undergo a phase change (such as solid-liquid or liquid-solid phase change) process within a specific temperature range. This phase change is accompanied by the absorption or release of latent heat, making PCMs a unique energy storage and transmission tool. The research on PCMs can be traced back decades, and one of its earliest applications was in cold chain logistics, for temperature control and stability of items such as medicines and food. However, in recent years, with the increasing focus on energy efficiency and sustainability, the research and application scope of PCMs has expanded to multiple fields.

[0003] In the construction industry, phase change materials are widely used to improve the thermal comfort and energy efficiency of buildings. They can be used in insulation materials, solar thermal collection systems, air conditioning systems, etc., by absorbing heat during the day and releasing heat at night, reducing the thermal fluctuations of the building, thereby reducing the energy consumption of the building. This is of great significance for reducing HVAC energy consumption and reducing carbon emissions.

[0004] Phase change sheet is a material with unique properties and a wide range of applications. Its research background can be traced back to multiple scientific and engineering fields. In the field of architecture, phase change sheet is widely used for thermal control and energy saving, which helps to reduce the energy consumption of buildings and improve indoor comfort. In the field of electronics, phase change sheet is used for heat dissipation and temperature control to improve equipment performance. In addition, phase change sheet is also widely used in food storage, medical equipment, transportation and other fields. Its unique energy storage and release characteristics make it a research and application hotspot in various fields.

[0005] The emergence of shapeable phase change materials provides a feasibility for making phase change plates, facilitates production, improves production efficiency, and reduces costs and time losses. Summary of the invention

[0006] The purpose of the present invention is to provide a shapeable phase change material and a preparation method thereof to provide basic materials for specific occasions and specific needs. To achieve the above purpose, the present invention provides the following technical solutions:

[0007] A shapeable phase change material, characterized in that the material is composed of epoxy resin, curing agent, and composite phase change material, and the mass percentage of each raw material to the total amount of raw materials is: epoxy resin is 3 / 24-8 / 24 (preferably 3 / 24-6 / 24, more preferably 4 / 24-5 / 24), curing agent is 1 / 24-2 / 24 (preferably 1 / 24-1.5 / 24, more preferably 1 / 24-1.2 / 24), and composite phase change material is the balance.

[0008] Furthermore, the composite phase change material is one or more of tetradecane microcapsules, pentadecane microcapsules, hexadecane microcapsules, heptadecane microcapsules, and octadecane microcapsules.

[0009] Furthermore, the phase change enthalpy of the composite phase change material ranges from 100 to 250 kJ / kg, and the phase change temperature ranges from 10°C to 68°C, preferably in the range of 18 to 32°C.

[0010] Furthermore, the phase change enthalpy of the shapeable phase change material ranges from 80 to 130 kJ / kg.

[0011] Furthermore, the phase change temperature range of the shapeable phase change material is 10°C-68°C, preferably in the range of 18-32°C.

[0012] Furthermore, the epoxy resin is one or more of water-based epoxy resins EP-301, EP-360, EP-365 and / or two-component epoxy resins E-44, E-51, E-58.

[0013] Furthermore, the curing agent is one or more of the fatty amine curing agents menthane diamine, isophorone diamine, and N-aminoethyl piperazine.

[0014] A method for preparing a shapeable phase change material, the specific preparation steps are as follows:

[0015] S1. Select one or more epoxy resins as raw material A, select one or more curing agents as raw material B, and mix raw material A and raw material B in a desired proportion;

[0016] S2, mixing the mixed raw material prepared in step S1 with the composite phase change material in a desired proportion, and stirring evenly with mechanical stirring;

[0017] S3, after the mixture stirred in step S2 is placed into a designated mold, refined in a vacuum environment for 2-4 hours, then taken out and placed at room temperature until solidified into a solid, and then demolded to obtain a fixed-shape phase change material.

[0018] Furthermore, the stirring time in the step is 1-2h, and the stirring speed is 300-1000r / min.

[0019] Furthermore, in step S3, the vacuum degree of the vacuum environment is -0.05 to -0.1 MPa; the room temperature environment is 20 to 25° C., and the standing time is 12 to 36 hours.

[0020] Furthermore, the shaped phase change material prepared in step S3 has uniform shape before and after melting, that is, the shape of the material remains consistent before and after melting, and the phase change material will not leak after melting.

[0021] The formed phase change material has no invisible change before and after the phase change, the phase change temperature and phase change enthalpy are adjustable, the stability is high, and the preparation process is simple, which is convenient for packaging and production, improves production efficiency, and reduces cost and time loss.

[0022] Compared with the prior art, the present invention has the characteristics of low process conditions, simple component ratio, easy operation of the preparation method, adjustable phase change temperature and phase change latent heat value, etc. In addition, the emergence of shapeable phase change materials provides a feasibility of making phase change plates, which is convenient to use.

[0023] The present invention uses epoxy resin, curing agent and composite phase change material as raw materials, and prepares the shapeable phase change material through a series of processes such as stirring and mixing. The formed shapeable phase change material has the controllable phase change temperature and stability; the material can be kneaded and deformed at will before shaping, and has a certain strength after shaping. At the same time, based on the phase change performance of the material, the shape of the material remains consistent before and after melting, and the phase change material will not leak; the preparation process is simple, easy to produce, improves production efficiency, reduces cost and time loss, and can be used in the field of phase change buildings to make phase change temperature-controlled bricks, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Differential scanning calorimetry curve of shape-fixable phase change material.

[0025] Figure 2 Actual picture of the shapeable phase change material used as phase change plate. DETAILED DESCRIPTION

[0026] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.

[0027] Example 1

[0028] Take 50g of epoxy resin E44 (Shandong Excellent Chemical Technology Co., Ltd.) and 10g of curing agent isophorone diamine (Oulian Hongda Industry and Trade Co., Ltd., curing agent IPDA) and mix them evenly; mix 60g of the obtained mixture with 180g of octadecane phase change microcapsules (Hefei Xinneng Phase Change New Material Technology Co., Ltd., microcapsule shell materials are made of melamine, silica, polyurea, polyurethane, PMMA, etc., the capsule particle size is small: between 0.5 microns and 3 microns, the capsule enthalpy value is high: the enthalpy value is greater than 180j / g), and stir evenly for 2h, the stirring speed is 500r / min, the mixture stirred in step S2 is placed in a rectangular mold, and then the mixture is placed in a vacuum oven with a vacuum degree of -0.1Mpa and reacted at room temperature of 25℃ for 2 hours, then taken out, and then allowed to stand at room temperature of 25℃ for 24h to make a phase change material with a fixed shape, and a phase change plate with a thickness of 2cm is obtained.

[0029] The differential scanning calorimetry curve of the obtained shaped phase change material is as follows: Figure 1 As shown in the figure, the phase change enthalpy value is 126.68 J / g and the phase change temperature is 26.39 °C. Figure 2 This material has no shape change before and after melting, and can be used in fields such as construction, and the operation is simple and convenient.

[0030] Example 2

[0031] Take 50g of epoxy resin E44 (Shandong Excellent Chemical Technology Co., Ltd.) and 10g of curing agent ipda (Oulian Hongda Industry and Trade Co., Ltd.) and mix them evenly; mix 60g of the obtained mixture with 200g of octadecane phase change microcapsules (Hefei Xinneng Phase Change New Material Technology Co., Ltd.), and stir evenly for 1h at a stirring speed of 500r / min. Put the mixture stirred in step S2 into a rectangular mold, and then put the mixture into a vacuum oven with a vacuum degree of -0.1Mpa at 25℃ for 1 hour, then take it out, and let it stand at 23℃ for 24h to make a phase change material with a fixed shape, and obtain a phase change plate with a thickness of 2cm.

[0032] The obtained shaped phase change material has a phase change enthalpy value of 116.40 J / g and a phase change temperature of 26.04° C. The material has no shape change before and after melting, can be used in construction and other fields, and is simple and convenient to operate.

[0033] Example 3

[0034] Take 50g of epoxy resin E44 (Shandong Excellent Chemical Technology Co., Ltd.) and 10g of curing agent ipda (Oulian Hongda Industry and Trade Co., Ltd.) and mix them evenly; mix 60g of the obtained mixture with 180g of hexadecane phase change microcapsules (Hefei Xinneng Phase Change New Material Technology Co., Ltd.), and stir evenly for 1h at a stirring speed of 500r / min. Put the mixture stirred in step S2 into a rectangular mold, and then put the mixture into a vacuum oven with a vacuum degree of -0.1Mpa at 23℃ for 1 hour, then take it out, and let it stand at 23℃ for 24h to make a phase change material with a fixed shape, and obtain a phase change plate with a thickness of 2cm.

[0035] The obtained shaped phase change material has a phase change enthalpy value of 122.40 J / g and a phase change temperature of 18.04° C. The material has no shape change before and after melting, can be used in construction and other fields, and is simple and convenient to operate.

[0036] Example 4

[0037] Take 100g of epoxy resin E44 (Shandong Excellent Chemical Technology Co., Ltd.) and 20g of curing agent ipda (Oulian Hongda Industry and Trade Co., Ltd.) and mix them evenly; mix 120g of the obtained mixture with 240g of heptadecane phase change microcapsules (Hefei Xinneng Phase Change New Material Technology Co., Ltd.), and stir evenly for 1h at a stirring speed of 700r / min. Put the mixture stirred in step S2 into a rectangular mold, and then put the mixture into a vacuum oven with a vacuum degree of -0.1Mpa at 21°C for 1 hour, then take it out, and let it stand at 23°C for 25h to make a phase change material with a fixed shape, and obtain a phase change plate with a thickness of 4cm.

[0038] The obtained shaped phase change material has a phase change enthalpy value of 82 J / g and a phase change temperature of 21.03° C. The material has no shape change before and after melting, can be used in construction and other fields, and is simple and convenient to operate.

[0039] Comparative Example 1

[0040] 200 g of octadecane microcapsules were taken and packaged. The phase change enthalpy was 162.92 J / g and the phase change temperature was 27.53°C. The material was in powder form before and after melting, with large deformation, and the overall shape could not be fixed.

[0041] Comparative Example 2

[0042] Invention patent: A carbon nanotube aerogel-based composite shaped phase change material and its preparation and application (CN114106779A) The carbon nanotube aerogel-based composite shaped phase change material mentioned in Example 1 is packaged. This material is a phase change material adsorbed in a carrier with a porous skeleton to form a composite phase change material. The material is granular before and after melting. The particle size depends on the size of the carrier, and the overall shape cannot be fixed.

Claims

1. A shapeable phase change material, characterized in that: The material is composed of epoxy resin, curing agent and composite phase change material, and the mass percentage of each raw material to the total amount of raw materials is: epoxy resin is 3 / 24-8 / 24 (preferably 3 / 24-6 / 24, more preferably 4 / 24-5 / 24), curing agent is 1 / 24-2 / 24 (preferably 1 / 24-1.5 / 24, more preferably 1 / 24-1.2 / 24), and composite phase change material is the balance.

2. The shape-setting phase change material according to claim 1, characterized in that: The composite phase change material is one or more of tetradecane microcapsules, pentadecane microcapsules, hexadecane microcapsules, heptadecane microcapsules and octadecane microcapsules.

3. The composite phase change material according to claim 1 or 2, characterized in that: The phase change enthalpy range of the composite phase change material is 100-250 kJ / kg, and the phase change temperature range is 10°C-68°C, preferably in the range of 18-32°C.

4. The shape-setting phase change material according to claim 1, characterized in that: The phase change enthalpy of the shapeable phase change material ranges from 80 to 130 kJ / kg; The phase change temperature range of the shape-setting phase change material is 10°C-68°C, preferably in the range of 18-32°C.

5. The shape-setting phase change material according to claim 1, characterized in that: The epoxy resin is one or more of waterborne epoxy resins EP-301, EP-360, EP-365 and / or two-component epoxy resins E-44, E-51, E-58.

6. The shape-setting phase change material according to claim 1, characterized in that: The curing agent is one or more of aliphatic amine curing agents such as menthane diamine, isophorone diamine and N-aminoethyl piperazine.

7. A method for preparing a shape-setting phase change material according to any one of claims 1 to 6, characterized in that: The specific preparation steps are as follows: S1. Select one or more epoxy resins as raw material A, select one or more curing agents as raw material B, and mix raw material A and raw material B in a desired proportion; S2, mixing the mixed raw material prepared in step S1 with the composite phase change material in a desired proportion, and stirring evenly with mechanical stirring; S3, after putting the mixture stirred in step S2 into a mold, refine it in a vacuum environment for 2-4 hours, then take it out and let it stand at room temperature until it solidifies into a solid, and then demold it to obtain a fixed-shape phase change material.

8. The preparation method according to claim 7, characterized in that: The stirring time in step S2 is 1-2h, and the stirring speed is 300-1000r / min; In step S3, the vacuum degree of the vacuum environment is -0.05 to -0.1 MPa; the room temperature environment is 20 to 25° C., and the standing time is 12 to 36 hours.

9. The preparation method according to claim 7 or 8, characterized in that: The shaped phase change material prepared in step S3 has uniform shape before and after melting, that is, the shape of the material remains consistent before and after melting, and the phase change material will not leak after melting.

10. A shapeable phase change material as claimed in any one of claims 1 to 6 which can be used to make phase change temperature-controlled bricks in phase change buildings.

Citation Information

Patent Citations

  • Carbon nanotube aerogel-based composite shaped phase change material and preparation and application thereof

    CN114106779A

  • Method for producing energy-saving scagliola containing microencapsulated phase change materials

    CN101633197A

  • Shape-stabilized phase change energy storage material with high-thermal conductivity and preparation method thereof

    CN102241963A

  • High-temperature-resistant epoxy resin composite phase change material and preparation method thereof

    CN106118608A

  • Composite phase change material and preparation method thereof as well as bituminous mixture

    CN108504039A